Hemopneumothorax associated with pneumorrachis following blunt chest trauma (Retracted) - Putu Eka Mardhika; Tjokorda Gde Bagus Mahadewa; Citra Aryanti (Neurologico Spinale Medico Chirurgico, 2020)
In late August 2020, we found that this article has previously been published elsewhere (Redundant publication). We then conducted the steps following COPE guidelines and we came to the conclusion that this article will be retracted from our journal (September 15th, 2020) A "retracted" watermark is already given to the article and the article will be retained online in order to maintain the scientific record. View retraction statement here